Metro and rapid transit delegate information : Wednesday 2 October 1996 (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of the infrarail 1996 seminar held in Manchester on 2 October 1996.